2016
DOI: 10.1128/aac.01654-15
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of SXT/R391-Related Integrative and Conjugative Elements Carrying bla CMY-2 in Proteus mirabilis Isolates from Gulls in the South of France

Abstract: The genetic structures involved in the dissemination of bla CMY-2 carried by Proteus mirabilis isolates recovered from different gull species in the South of France were characterized and compared to clinical isolates. bla CMY-2 was identified in P. mirabilis isolates from 27/93 yellow-legged gulls and from 37/65 slender-billed gulls. It was carried by a conjugative SXT/R391-like integrative and conjugative element (ICE) in all avian strains and in 3/7 human strains. Two clinical isolates had the same genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
4
9
0
2
Order By: Relevance
“…In contrast, no dominant β-lactamase genes are carried by ICE Pmi Chn117, suggesting that the class A β-lactamase gene might have been obtained via horizontal gene transfer or recombination. In summary, our study reported multi-drug resistance, including the increasing prevalence of class A β-lactamase-producing P. mirabilis , which is consistent with the trends in Japan16, Taiwan39 and other reports2440. In conclusion, our results present abundant genetic diversity and multidrug resistance of ICEs carried by Proteus strains from both food sources and diarrhoeal patients.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, no dominant β-lactamase genes are carried by ICE Pmi Chn117, suggesting that the class A β-lactamase gene might have been obtained via horizontal gene transfer or recombination. In summary, our study reported multi-drug resistance, including the increasing prevalence of class A β-lactamase-producing P. mirabilis , which is consistent with the trends in Japan16, Taiwan39 and other reports2440. In conclusion, our results present abundant genetic diversity and multidrug resistance of ICEs carried by Proteus strains from both food sources and diarrhoeal patients.…”
Section: Discussionsupporting
confidence: 90%
“…They carry genes coding for the resistance to sulfamethoxazole, trimethoprim, chloramphenicol, mercury, streptomycin and kanamycin, as well as β-lactamases genes [bla HMS−1 (Ryan et al, 2017), bla CMY−2 (Harada et al, 2010), bla CTX−M−2 (Mata et al, 2011)]. SXT/R391-type ICEs have been identified in strains of P. mirabilis not only in Asia (Li et al, 2016) but also in Spain (Mata et al, 2011) and in France (Aberkane et al, 2016). They are easily transferable by conjugation of P. mirabilis to E. coli, K. pneumoniae, Salmonella enterica serovar Typhimurium, or Citrobacter koseri (Harada et al, 2010) (Figures 2, 3).…”
Section: Integrative Conjugative Elements (Ices)mentioning
confidence: 99%
“…In the transposition module called Tn6093, ISEcp1 is located 110-bp upstream of the bla CMY gene, and contains fragments of C. freundii chromosome on a ColE1-type plasmid (D'Andrea et al, 2011) (Figure 2). Mobilization of the bla CMY−2 gene by integrative and conjugative islands (ICE) has also been described in Asia (Li et al, 2016), Spain (Mata et al, 2011), and France (Aberkane et al, 2016), in Proteus isolates from humans (Harada et al, 2010) or from livestock, wild animals and pets. The bla CMY−2 gene has also been described in Switzerland from chicken raw meat on a IncI1 plasmid (Seiffert et al, 2013).…”
Section: Cmy Enzymesmentioning
confidence: 99%
“…Of particular interest and prevalence, the variant ICEPmiJpn1, originally identified in Japan, carries a CMY-2 beta-lactamase gene (Harada et al, 2010). This particular variant of SXT/R391 ICEs was subsequently identified in P. mirabilis isolates from human and animal origins in Spain, India, France, China, and Ireland (Mata et al, 2011;Aberkane et al, 2016;Lei et al, 2016;Mac Aogáin et al, 2016;Bie et al, 2017).…”
Section: Introductionmentioning
confidence: 99%